The effectiveness of the SQ3R reading strategy in enhancing students' reading comprehension abilities / Lalitha Balakrishnan Nair - Balakrishnan Nair, Lalitha (2008)
The main aim of this study was to investigate the effectiveness of SQ3R Reading Strategy in enhancing students' reading comprehension ability. The study involved a group of diploma in business students at Universiti Teknologi MARA Sarawak. The study employed a quasi-experimental research design which engaged an experimental group and a control group with 30 students in each group. The experimental group was given direct and explicit instruction in the use of the SQ3R Reading Strategy for a period of 32 hours, focusing on training students in seven (7) specific reading skills which included predicting, skimming, scanning and locating main ideas, making inferences, distinguishing between facts and opinions, identifying main ideas and supporting details, and drawing conclusions. The perceptions of the students in the experimental group were assessed by means of a 25-likert scale SQ3R Questionnaire. Semistructured interviews were also conducted not only on the students but also the lecturer involved in teaching the SQ3R reading strategy. The quantitative data collected was analysed using SPSS 13.0 for descriptive statistics whereas the qualitative interview data was analysed inductively and deductively before any final conclusions were made. The two groups were also given a pre-test and a post-test to investigate the reading comprehension performance of the two groups. The test scores were analysed using Wilcoxon test for significant difference. The findings indicated that both the students in the experimental group and the lecturer perceived the SQ3R reading strategy positively despite a few challenges. The non-parametric Wilcoxon Matched-Pairs Signed-Rank test results on the pre and post tests indicated that there was a significant increase in means scores of the students in the experimental group indicating the effectiveness of the SQ3R reading strategy. Furthermore further analysis on the performance of the two groups on the seven specific reading skills also indicated that the students in the experimental group outperformed the control group by recording significant differences in almost all the questions except in making inferences and drawing conclusions. This study seems to suggest that SQ3R strategy is an effective reading strategy in enhancing students' reading comprehension ability.